Time-Optimal Two-Channel Control of Interrelated Objects with Distributed Parameters - Rapoport, E. Ya; Ilina, N. A. (Optoelectronics, instrumentation, and data processing, 2022)
A constructive method is proposed for solving the problem of time-optimal two-channel boundary control of two physically inhomogeneous objects with distributed parameters described by linear heat conduction equations under conditions of a perfect thermal contact of interacting media with estimates of the target sets of controlled temperature fields in a uniform metric that are typical for engineering applications. The developed technique uses a special method for describing the studied temperature fields in a form containing uniformly converging series. The approach under development is based on the parameterization procedure for the desired control actions and the subsequent reduction to the problem of semi-infinite optimization, which is solved by the scheme of the alternance method under the additional restriction on the same duration of the control process for both control actions.